Plain front façade with a flanking chhajja supporting the roof - Temples of India Project Team (Jio Institute, 2024)
The east-facing entrance leading to the mulaprasada has a plain and simple base, with a few steps paving the entrance, and a single decorative band at the top. The front façade is plain, with a flanking chhajja supporting the roof. These architectural features are additions made in the 19th century resulting in the present look of the temple.